ANALYSIS SOCIAL ANXIETY IN HIGH SCHOOL STUDENTS (Description of Public High School Students’ Social Anxiety in Indihiang District) - Rana Dianah (Psikoeduko: Jurnal Psikologi Edukasi dan Konseling, 2023)
The purpose of this study was to determine the description of social anxiety in high school students in Indihiang District, Tasikmalaya City, based on gender, differences in social anxiety based on majors as a benchmark for designing guidance and counseling services to reduce social anxiety in students. This study uses a quantitative descriptive approach to reveal the description of social anxiety in students. The data collection technique used was incidental sampling, which is a sampling technique based on chance, meaning that anyone who meets the researcher by chance can be used as a sample. The data analysis technique uses the calculation of the distribution of data through the calculation of the average and standard deviation, as well as the calculation of percentages and the SPSS 24.00 program for windows to test the difference between two paired averages. In this study the sample obtained was 642 students. The results of this study indicate that social anxiety in high school students in Indihiang District, Tasikmalaya City, out of a total of 642 students, obtained a low category score with a percentage of 12% (79 students), in the high category with a percentage of 17% (109 students), and the medium category obtained a score the highest is 71% (454 students).